2023
DOI: 10.1007/s40121-023-00808-y
|View full text |Cite
|
Sign up to set email alerts
|

A Reservoir Computing with Boosted Topology Model to Predict Encephalitis and Mortality for Patients with Severe Fever with Thrombocytopenia Syndrome: A Retrospective Multicenter Study

Abstract: Introduction Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne virus associated with a high rate of mortality, as well as encephalitis. We aim to develop and validate a machine learning model to early predict the potential life-threatening conditions of SFTS. Methods The clinical presentation, demographic information, and laboratory parameters from 327 patients with SFTS at admission in three large tertiary hospitals in Jiangsu, China b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…We only identified two studies on the relationship between blood lipid profiles and SFTS prognosis. In a study using machine learning methods, Zheng et al reported that serum cholesterol may be a relevant indicator of mortality in patients with SFTS ( Zheng et al, 2023 ). Huang et al suggested an association between low serum HDL-C levels and adverse outcomes in SFTS ( Huang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…We only identified two studies on the relationship between blood lipid profiles and SFTS prognosis. In a study using machine learning methods, Zheng et al reported that serum cholesterol may be a relevant indicator of mortality in patients with SFTS ( Zheng et al, 2023 ). Huang et al suggested an association between low serum HDL-C levels and adverse outcomes in SFTS ( Huang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under different polarization angles, only Excos(θp) and Eysin(θp) can pass through the TWP, and the total feedback light can be described as Ef=Excos(θp)+Eysin(θp) [6]. Considering the feedback delay, the two polarization components of the feedback light can be written as: According to the spin-flip model (SFM), the states of the VCSEL-based reservoir under arbitrary polarization angle feedback can be expressed as: [7] 0 ( ) 2…”
Section: Theory and System Modelmentioning
confidence: 99%